Clinical characteristics and risk factors of late-stage lung adenocarcinoma patients with bacterial pulmonary infection and its relationship with cellular immune function - Yang, Kangli; Wei, Haiting; Zhu, Weiwei; Xu, Yapeng; Wang, Shuaifeng; Fan, Feifei; Zhang, Kai; Yuan, Qing; Wang, Hongmin (Frontiers in Immunology, 2025)
BackgroundTo research the clinical characteristics, risk factors, the correlation between bacterial pulmonary infection and immune function of advanced lung adenocarcinoma patients complicated with bacterial pulmonary infection.Methods334 stage III and IV lung adenocarcinoma patients admitted to the first affiliated hospital of Zhengzhou University from January 2020 to March 2023 were selected and divided into an infection group (n = 240) and a control group (n= 72) according to whether complicated with bacterial pulmonary infection. The clinical characteristics were analyzed. The pulmonary microbiota and human T lymphocyte subsets (CD3+, CD4+, CD8+) were detected. Multivariate logistic regression analysis was performed to explore the risk factors for pulmonary bacterial infection in advanced lung adenocarcinoma patients.ResultsAmong 334 patients, 264 cases were complicated with pulmonary bacterial infection, and 70 cases had no pulmonary bacterial infection. In total, 544 pathogenic bacteria were isolated from the patients. Of these, 170 strains (31.25%) were Gram-negative bacilli, 162 strains (29.78%) were Gram-positive cocci, 27 strains (4.96%) Gram-positive bacilli. There were statistically significant differences in age, smoking, combined diseases, TNM staging, CD3+ T cell percentage, and CD4+ T cell percentage between the two groups (P < 0.05). Multivariate logistic regression analysis revealed smoking, bronchiectasis, and diabetes were independent risk factors leading to late-stage lung adenocarcinoma patients with bacterial pulmonary infection (P < 0.05). In those patients on immune checkpoint inhibitors, the lung Gram-positive group has a higher number of CD4+ T cells and CD4+/CD8+ T cell ratio than the Gram-negative group (P < 0.05).ConclusionSmoking, bronchiectasis, and diabetes are risk factors for lung bacterial infection in patients with advanced lung adenocarcinoma. The effect of immune checkpoint inhibitor treatment on T cells is more pronounced in Gram positive bacteria.